2016
DOI: 10.1097/fbp.0000000000000219
|View full text |Cite
|
Sign up to set email alerts
|

A dose–response study of separate and combined effects of the serotonin agonist 8-OH-DPAT and the dopamine agonist quinpirole on locomotor sensitization, cross-sensitization, and conditioned activity

Abstract: Chronic treatment with the dopamine D2/D3 agonist, quinpirole, or the serotonin 1A agonist, 8-hydroxy-2-(di-n-propylamino)-tetralin (8-OH-DPAT), induces behavioral sensitization. It is not known whether both drugs produce sensitization through a shared mechanism. Here, we examine whether quinpirole and 8-OH-DPAT show cross-sensitization and impact sensitization, as would be expected from shared mechanisms. Male rats (N=208) were assigned randomly to 16 groups formed by crossing four doses of quinpirole (0, 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 69 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…The A11 nucleus contains almost 2.5 times more GABA-containing neurons as compared with dopamine-containing neurons, and noxious facial stimulation activates GABA-containing neurons in the A11 nucleus [15], suggesting that GABA-containing neurons in the A11 nucleus might be involved in the regulation of dopaminergic neuron activity. Dopamine D2 agonist and GABA A receptor agonist were reported to affect motor function [33][34][35][36]. Therefore, the change of head-withdrawal threshold measured in our study might be the result of not only attenuation of mechanical hypersensitivity but also change of motor function by quinpirole and muscimol.…”
Section: Discussionmentioning
confidence: 64%
“…The A11 nucleus contains almost 2.5 times more GABA-containing neurons as compared with dopamine-containing neurons, and noxious facial stimulation activates GABA-containing neurons in the A11 nucleus [15], suggesting that GABA-containing neurons in the A11 nucleus might be involved in the regulation of dopaminergic neuron activity. Dopamine D2 agonist and GABA A receptor agonist were reported to affect motor function [33][34][35][36]. Therefore, the change of head-withdrawal threshold measured in our study might be the result of not only attenuation of mechanical hypersensitivity but also change of motor function by quinpirole and muscimol.…”
Section: Discussionmentioning
confidence: 64%
“…If the drug application was discontinued after the end of the habituation phase, sensitization to 8-OH-DPAT during habituation had no effect on spatial performance and locomotion during acquisition. Contrarily, Johnson and Szechtman [39] found that chronic administration of 8-OH-DPAT at low doses (0.0625, 0.125 mg/kg) per 8 days produced hyperlocomotion and compulsive checking even when tested after several days without the 8-OH-DPAT. However, it should be noted that the difference between spontaneous behavior (open field) and motivated behavior (carousel maze) might add up to the divergence of results.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, using the 2-deoxyglucose technique to measure local cerebral glucose utilization in quinpirole-sensitized animals (Carpenter et al, 2003;Richards et al, 2005), alterations had been found in cortical (the cingulate -4-cortex-area 1, frontal cortex-area 3, lateral orbital cortex, medial/ventral orbital cortex, and parietal cortex) and subcortical areas (ventral pallidum and nucleus accumbens); more recently, changes in the cortico-striato-thalamico-cortical circuit had been observed by PET neuroimaging in quinpirole-sensitized rats (Servaes et al, 2016). Others report in quinpirole-sensitized animals: increased high-affinity states of dopamine D2 receptors (D2 High ) (Seeman et al, 2006;Perreault et al, 2007;Culver et al, 2008); decreased dopamine levels in the left pre-frontal cortex (Sullivan et al, 1998); reduced dopamine and glutamate neurotransmission in the nucleus accumbens (Escobar et al, 2015); as well alterations in dopamine-serotonin interaction (Alkhatib et al, 2013;Tucci et al, 2013;Johnson and Szechtman, 2016). However, it remains to be established which of those findings, if any, are necessary for the pathophysiology of compulsive checking (Szechtman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%